Risking life and limb in the global economy: Scrap metal price and landmine/UXO incidents in Cambodia. (March 2016) - Roberts, Wade; Bilginsoy, Cihan
Highlights: Handling landmine/UXO to sell as scrap metal in Cambodia is price responsive. The price does not affect other types of encounters with ordnance. People should be compensated to induce them to report discovered landmine/UXO. Abstract: Collecting leftover landmines and UXO to sell them to metal scrap yards is an important source of cash income for many people in former theaters of military conflict. It also exposes the scrappers to bodily harm. While the role of financial incentives is recognized by landmine/UXO action organizations, the impact of economic factors on the prevalence of landmine/UXO incidents has not yet been subjected to quantitative analysis. In this paper we address this gap by estimating the elasticity of landmine/UXO incidents in Cambodia with respect to the scrap metal price. We hypothesize that handling landmine/UXO for scrapping purposes (tampering) is price elastic while handling for non-financial purposes or unwitting encounters (accidents) is price inelastic. We test these hypotheses using a unique monthly scrap metal price series collected from final scrapyards on the Thai border. Our study finds supporting evidence for both hypotheses: the elasticity of tampering is unitary while the elasticity of accidents is not different from zero. An important component of mitigating landmine/UXO incidents in Cambodia is the removal of explosive ordnance by specialized teams in situ after these explosive remnants of war are discovered and reported by local villagers. Our findings suggest that the success of these operations requires rewarding villagers by giving them claim over the metal fragments or paying them a competitive price for metal because otherwise villagers would have less of an incentive to report discovered ordnance.